Proyecto De Inversión Para La Industrialización De Café Para La Asociación Agroartesanal De Productores Ecológicos De Café Especial Del Cantón Loja “Apecael” En La Parroquia San Pedro De Vilcabamba, Cantón Loja. - Mosquera González, Jefferson Vinicio (2016)
This thesis is framed in the development of an industrializing coffee company with which aside from giving an added value to coffee and thereby provide a stable and fair price to producers , also aims to give people a product organic optimum quality in terms of physical and organoleptic characteristics. With this project the feasibility of creating the company mentioned, developing relevant studies to prove it, so be evident : Market Research, with which can be analyzed Competition, Demand and establish strategies with which our product will be positioned in the market, creating a cost leadership and differentiation giving added value to the final product. The Technical Study with which we have identified the equipment, machinery, raw materials and facilities required for the project and, therefore, investment costs and operating required as well as working capital is needed. The Financial Study which helped us to identify, organize and systematize the information of a monetary nature, ie, all items of investments, income and expenses may be deducted from the previous studies, to develop the analytical tables and additional data in order to evaluate the project and determine its profitability. Through legal study determined the feasibility of a project in light of the Development Plans, Territorial Planning, budgeting rules related to location, environmental, use of patents, tax law, labor issues and contracting necessary for the respective operating permits, contracts for the purchase, sale, working etc. Finally according to the conclusions we have reached the most prominent and crucial to the successful implementation and management of industrializing coffee company recommendations.